PENERAPAN MEDIA PEMBELAJARAN JEPITAN DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PADA ANAK USIA DINI - Nurlela Siagian; Euis Eti Rohaeti; Sharina Munggaraning Westhisi (IKIP Siliwangi, 2019)
The importance of numeracy skills for early childhood does not need to be doubted, because almost every life can not be separated from the calculated dimensions of counting. Media has an important role in learning, one of which is a clip that can develop numeracy skills in children. From the results of observations made, 18 out of 25 children still cannot master numeracy. This study used a quasi-experimental method involving 5-6 years old B group children with two classes namely the executive class and control. From the results of the study before applying it (pre test) the results of the normality tests of the experimental and control classes showed results of 0.021 <0.05 and the normality results of the control class 0.012 <0.05, the experimental Pre Test results and controls were not normally distributed. When viewed from the results of the Mann Withney test that the Mann Whitney Pre Test there were no differences in the initial abilities of the control class and the experimental class. Then from the results of the Man Whitney Post Test the experimental and control classes 0,000 because <0.05 the results of the Man Whitney Post Test there were differences in the ability to count after being given treatment. From the results of the Pre Test and Post Test. The conclusion of this study is that the tongs learning media can improve numeracy skills in early childhood.Pentingnya kemampuan berhitung untuk anak usia dini tidak perlu diragukan lagi, sebab hampir setiap kehidupan tidak mungkin lepas dari dimensi hitung menghitung. Media memiliki peranan penting dalam pembelajaran salah satunya jepitan yang dapat mengembangkan kemampuan berhitung pada anak. Dari hasil observasi yang telah dilakukan, 18 dari 25 anak masih belum bisa menguasai berhitung. Penelitian ini menggunakan metode kuasi eksperimen yang melibatkan anak usia dini kelompok B usia 5-6 tahun dengan dua kelas yaitu kelas ekprimen dan kontrol. Dari hasil penelitian sebelum diterapkannya (pre tes) hasil dari uji normalitas kelas eksperimen dan kontrol menunjukkan hasil 0,021 0,05 dan hasil normalitas dari kelas kontrol 0.012 0,05 maka data hasil Pre Test eksperimen dan kontrol sama-sama tidak berdistribusi normal. Jika dilihat dari hasil uji Mann Withney bahwa Pre Test Mann Whitney tidak terdapat perbedaan kemampuan awal dari kelas kontrol maupun kelas eksperimen. Kemudian dari hasil Post Test uji Man Whitney kelas ekperimen dan kontrol 0,000 karena 0,05 hasil Post Test Man Whitney terdapat perbedaan kemamampuan berhitung setelah diberikan perlakuan. Dari hasil Pre Test dan Post Test. Kesimpulan dari penelitian ini bahwa media pembelajaran jepitan dapat meningkatkan kemampuan berhitung pada anak usia dini.